Indigenous literacy of local knowledge about the signs of natural disaster A case of Way Ela Natural Dam - Maluku - Edwin Rizal; Rizki Nurislaminingsih (Perpustakaan Universitas Gadjah Mada, 2023)
Introduction. Various natural disasters occurred in Maluku, with one of the impacts is changing the land surface. One example is a forest has changed into a hill or a river has changed into a natural dam. In Maluku, Way Ela natural dam was formed as a resultof the disaster in 2012 and was destroyed again by the disaster in 2013. This natural event that occurred in a relatively short period of time is still remembered by the community. This study aims to explore the types of local knowledge about dam disasters based on their memories. Data Collection Method. Data collection in this study was conducted by the interviews. Data Analysis. Data were analyzed by grouping the themes on natural signs of the formation and of the broken of the dam. Results and Discussion. The formation of dams begins with earthquakes, landslides, dry rivers, and strange animal behavior. Natural signs before a broken-down dam are earthquakes, heavy rain, cracked ground, strange behavior of animals, and changes in cooler air temperature. Conclusion. This study concludes that the community is aware of three types of disaster signs including the formation of a dam, before the dam breaks, and when the dam breaks.